Determinan return saham pada perusahaan manufaktur periode 2016-2020 dengan analisis rasio keuangan - Subur Karyatun (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of liquidity, profitability, and solvency on stock returns in manufacturing companies for the 2016-2020 period. The data in this study uses secondary data in the form of financial reports that meet the criteria. The technique used in the analysis in this study was panel data linear regression using the EVIEWS 10 program. The test results using panel data regression with the EVIEWS 10 tool yielded only two of the three independent variables that had a significant effect on stock returns. Profitability as measured by return on equity and solvency as measured by the debt to equity ratio predicts stock returns in a positive direction. Meanwhile, liquidity as measured by the current ratio has no effect on stock returns. Investment in the manufacturing sector which is a capital-intensive company requires financing to develop the business so that a high solvency value can reflect a better stock return.